in situ Chemical Synthesis of PANI by Using Aromatic Carboxylic Acid as Dopant for Detection of Ammonia at Room Temperature - Ganapati Khanapure, Renukacharya; Kashinath Awate, Sharad; Vasant Patil, Suresh (Asian Journal of Chemistry, 2021)
In this work, polyaniline (PANI) film was successfully synthesized by in situ chemical polymerization technique by using aromatic carboxylic acids like benzoic acid, p-methoxybenzoic acid and p-nitrobenzoic acid, doped in presence of ammonium persulphate as an oxidant. Electric conductivity study of doped polyaniline has been studied concerning temperature. Surface composition morphology and structure of synthesized carboxylic acid doped polyaniline were characterized via different methods such as the electrical conductivity by two probes, UV-vis spectroscopy, FTIR spectroscopy, X-ray diffraction (XRD) and scanning electron microscopy (SEM). The PANI based ammonia gas sensor was synthesized by using, benzoic acid, p-methoxybenzoic acid and p-nitrobenzoic acid as dopant which has excellent selectivity towards NH3 and 28, 426 and 327% response of ammonia gas at 100 ppm concentration, respectively at room temperature.